International Financial Reporting Standards and Earnings Management in Latin America - Alex Augusto Timm Rathke; Verônica de Fátima Santana; Isabel Maria Estima Costa Lourenço; Flávia Zóboli Dalmácio (RAC: Revista de Administração Contemporânea, 2016)
This study analyzes the level of earnings management in Latin America after the adoption of the International Financial Reporting Standards (IFRS) and analyzes the role of cross-listing in the United States. The literature on earnings management in less developed countries is still under construction, and few studies focus on this issue, especially with respect to Latin America, despite its relevant role in the global economy. This paper fills this gap in the literature as it analyzes the level of IFRS earnings management regarding the first and main Latin American countries applying IFRS (Brazil and Chile), when compared to the main Anglo-Saxon countries with IFRS tradition (United Kingdom and Australia), and with the main Continental European economies (France and Germany). The results show that Latin American firms present a higher level of earnings management than Continental European and Anglo-Saxon firms, and this opportunistic behavior remains significant when only global players with cross-listing in the United States are analyzed. Thus, even with a unique set of high quality accounting standards (IFRS) and strong reporting incentives, countries’ specific characteristics still play an important role in the way IFRS is implemented in each country.